Board Components and Quality of Financial Reporting: Mediating Effect of Audit Quality - QAWQZEH, HAMZA KAMEL; ENDUT, WAN ANISAH; RASHID, NORFADZILAH (The journal of contemporary issues in business and government, 2021)
The main purpose of this study is to investigate the mediating effect of audit fees as an indicator of audit quality on the board components, the directors' remunerations, and the financial reporting quality in the Jordanian context. This study used Panel Data of 180 listed firms in Amman Stock Exchange from 2009 to 2017. The collected data were analyzed using the multiple regression analysis and Causal Steps Method. The results showed that the larger size of the board and independent directors on the board have a negative and significant influence on FRQ, whereas the board expertise and directors’ remuneration have a significantly positive impact on FRQ, as supported by the Agency Theory. Regarding the audit quality, the results revealed that the board size, the board independence and the directors’ remunerations have a positive and significant effect on the audit fees as an indicator of the audit quality. In contrast, the board expertise has significantly negative impact on the audit fees, and the audit quality has a partial mediating effect on the relationship of board components with FRQ. The findings are particularly important for the shareholders and regulators in introducing new legislations regarding the board composition and audit profession, increasing the monitoring role of the independent directors and large boards on the managerial performance when preparing the financial reports and highlighting the interaction between the board effectiveness and audit quality in restricting the EM practices and ensuring FRQ in one of the developing countries (Jordan). It is shown that the factors affecting FRQ can definitely enhance their ability through the interaction with the external factors to achieve the role of board of directors in in reducing the financial fraudulent. Originality/value – To the best knowledge of the authors, the current study is one of the first studies that addresses the directors’ remuneration and the mediating effect of the audit fees in the relationship between the board components and FRQ in Jordan and the Middle East.